Endovascular stent graft repair of abdominal aortic aneurysms: Current status and future directions - Sun, Zhonghua (Baishideng, 2009)
Endovascular stent graft repair of abdominal aortic aneurysm (AAA) has undergone rapid developments since it was introduced in early 1990s. Two main types of aortic stent grafts have been developed and are currently being used in clinical practice to deal with patients with complicated or unsuitable aneurysm necks, namely, suprarenal and fenestrated stent grafts. Helical computed tomography (CT) angiography has been widely recognized as the method of choice for both pre-operative planning and post-operative follow-up of endovascular repair. In addition to 2D axial images, a number of 2D and 3D reconstructions are generated to provide additional information about imaging of the stent grafts in relation to the aortic aneurysm diameter and extent, encroachment of stent wires to the renal artery ostium and position of the fenestrated vessel stents.The purpose of this article is to provide an overview of applications of endovascular repair of AAA and diagnostic applications of 2D and 3D image visualizations in the assessment of treatment outcomes of endovascular repair. Interference of stent wires with renal blood flow from hemodynamic point of view will also be discussed, and future directions explored.